Antifungal efficacy of floral extracts, biocontrol agents and fungicides against Fusarium oxysporum f.sp. ciceri - AMOL V. SHITOLE*, SHIVAJI H. WAVARE, R.M. GADE and (Indian Phytopathology, 2017)
The present investigation was conducted during 2011-2015 to evaluate the effectiveness of extracts of Marigold sp. (Tagetes erecta L.), Gaillardia sp. (Gaillardia pulchella), Chrysanthemum sp. (Chrysanthemum indicum) and Calotropis sp. (Calotropis gigantea) flowers, biocontrol agents and fungicides against Fusarium oxysporum f.sp. ciceri. Among the Pseudomonas fluorescens, Bacillus subtilis and Trichoderma harzianum tested by dual culture technique, P. fluorescens suppressed the colonisation of F. oxysporum f. sp. ciceri by 81.59%.The three fungicides viz., carbendazim (0.1%), metalaxyl (0.2%) and thiram (0.2%) were tested by poisoned food technique. Carbendazim @ 0.1% showed the highest effectiveness against F. oxysporum f. sp. ciceri. Seed treatment with P. fluorescens 10 g/kg seed + Trichoderma harzianum 4 g/kg seed + Marigold sp. (Tagetes erecta L.) floral water extract 4% proved highly effective in increasing seedling vigour index (3008.25) in chickpea in paper towel assay and was also effective to reduce incidence of Fusarium wilt (69.31%) under green house conditions.